2004
DOI: 10.2165/00019053-200422060-00003
|View full text |Cite
|
Sign up to set email alerts
|

Economic Implications of Treatment-Resistant Depression Among Employees

Abstract: TRD has gained increasing recognition due to both the clinical challenges and economic burdens associated with the condition. TRD imposes a significant economic burden on an employer. TRD-likely employees are more likely to be treated for selected comorbid conditions and have higher medical and work loss costs across all conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 18 publications
4
64
1
2
Order By: Relevance
“…Previous research indicated that depression has a significant economic impact on medical care costs [19] and worker productivity [20], although such studies do not typically control for personality pathology. Given the significant increase in treatment utilization by patients in the BPD group over utilization by patients in the MAD group, the economic impact of a BPD diagnosis is likely considerable.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicated that depression has a significant economic impact on medical care costs [19] and worker productivity [20], although such studies do not typically control for personality pathology. Given the significant increase in treatment utilization by patients in the BPD group over utilization by patients in the MAD group, the economic impact of a BPD diagnosis is likely considerable.…”
Section: Discussionmentioning
confidence: 99%
“…It is expected to become the second most common cause of disability worldwide by 2015 with obvious socio-economic implications (Strekalova et al, 2011). Traditional pharmacotherapy which focuses on increasing monoamines (norepinephrine or serotonin) neurotransmission has a relatively slow onset (Kupfer et al, 1989) of action and it has a limited effectiveness, between 10 and 20% of the treated patients do not respond to any antidepressant medication (Greenberg et al, 2004). Recent clinical studies have shown that a single subanesthetic dosage of the non-competitive N-methyl-Daspartate receptor (NMDARs) antagonist, ketamine, produces a rapid and lasting antidepressant effect in patients who were resistant to the current treatment (Maeng et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although several therapeutic interventions have proven their effectiveness, some depressed patients (10 up to 20 %) receiving antidepressant medication are partially or totally resistant to treatment (Greenberg et al, 2004). For this group of drug-resistant patients alternative and effective therapeutic options are therefore required.…”
Section: Introductionmentioning
confidence: 99%